2019
DOI: 10.1021/acs.organomet.9b00134
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric, Divalent Vanadium Bis(arylamido) Complexes: Linkage Isomerism and Reactivity

Abstract: Divalent complexes of vanadium were synthesized employing bulky silyl(aryl)amido ligands −N(Si i Pr 3 )DIPP and −N(Si t Bu 2 Me)DIPP (DIPP = 2,6-i Pr 2 C 6 H 3 ). Solid-state structural characterization revealed that although the ligand −N-(Si i Pr 3 )DIPP supports a monomeric, bis(amido) complex of vanadium, its constitutional isomer −N(Si t Bu 2 Me)DIPP affords a homoleptic complex in which the vanadium center is sandwiched between the arene rings, an unusual binding mode for arylamido ligands. Magnetometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…Similarly, salt‐like compounds, such as KN(SiMe 3 ) 2 or KCH 2 Ph, form interesting at‐complexes (e. g. [KM(CH 2 Ph){N(SiMe 3 ) 2 } 2 ] or [KFe{N(SiMe 3 ) 2 } 3 ]), which evoke distinct reactivities [18,19] . In addition to hexamethyldisilazanides, metal(II) complexes with bulkier silyamide ligands (e. g. −N(SiMe 2 Ph) or −N(Dipp)SiR 3 ) (Dipp=2,6‐di‐ iso ‐propylphenyl) also found their use with a persistent quasilinear geometry [20–25] . In recent reports it was also shown that such divalent 3d‐metal silylamides can be reduced giving linear, monovalent complex anions [22,25–29] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, salt‐like compounds, such as KN(SiMe 3 ) 2 or KCH 2 Ph, form interesting at‐complexes (e. g. [KM(CH 2 Ph){N(SiMe 3 ) 2 } 2 ] or [KFe{N(SiMe 3 ) 2 } 3 ]), which evoke distinct reactivities [18,19] . In addition to hexamethyldisilazanides, metal(II) complexes with bulkier silyamide ligands (e. g. −N(SiMe 2 Ph) or −N(Dipp)SiR 3 ) (Dipp=2,6‐di‐ iso ‐propylphenyl) also found their use with a persistent quasilinear geometry [20–25] . In recent reports it was also shown that such divalent 3d‐metal silylamides can be reduced giving linear, monovalent complex anions [22,25–29] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to hexamethyldisilazanides, metal(II) complexes with bulkier silyamide ligands (e. g. −N(SiMe 2 Ph) or −N(Dipp)SiR 3 ) (Dipp=2,6‐di‐ iso ‐propylphenyl) also found their use with a persistent quasilinear geometry [20–25] . In recent reports it was also shown that such divalent 3d‐metal silylamides can be reduced giving linear, monovalent complex anions [22,25–29] . These were employed in bond activation and substrate reduction [19,24,27,29–34] .…”
Section: Introductionmentioning
confidence: 99%
“…Curious as to the true importance of the chelating arm in these systems in forming reactive systems G and H , we sought to develop closely related systems utilising the monodentate bulky amide SiiP Dipp ( SiiP Dipp = [Dipp( i Pr 3 Si)N] − ). 13 Herein we report on the resulting cationic tetrylene nickel(0) complexes, [ SiiP DippE·Ni(PPh 3 ) 3 ] + (E = Ge ( 4 ) and Sn ( 5 )), which feature linear L-E–Ni bonding interactions which are best described as donor–acceptor E–M triple bonds. This gives clear evidence that the chelating phosphine arms in G and H do indeed lead to a reduced bond order in those compounds, thus amplifying their reactivity.…”
mentioning
confidence: 99%
“…Curie fits of SQUID magnetic measurements afforded magnetic moments of 3.36 (1) and 4.68 (2) µB, consistent with high-spin configurations. These values are lower than the spinonly values of 3.88 and 4.90 µB expected for d 3 and d 4 complexes, suggesting a significant unquenched orbital angular momentum contribution to the overall moment, which is lower as a result of the positive spinorbit coupling constants.Only four such complexes are known for vanadium (the first of which was not reported until 2013), 14,15 although several low-valent complexes of higher coordination at vanadium are known. 8,[15][16][17][18][19] Neutral twocoordinate complexes of chromium are more numerous, with ca.…”
mentioning
confidence: 99%
“…-N(Si i Pr3)Dipp, Dipp = 2,6diisopropylphenyl). 15 Because of these difficulties, investigations of the chemistry and properties of two-coordinate openshell (d 1 -d 9 ) transition metal complexes have mainly focused on species in which the d-valence shell is at least half full (i.e. d 5 -d 9 ).…”
mentioning
confidence: 99%